2008
DOI: 10.1055/s-0028-1102902
|View full text |Cite
|
Sign up to set email alerts
|

Follicular Unit Transplantation

Abstract: Follicular unit transplantation (FUT) is the culmination of decades of refinement and evolution of hair transplantation techniques. Hair naturally grows in groups of one to four individual follicles separated by intervening soft tissue. These clumps or groups of hairs are termed FOLLICULAR UNITS. FUT uses microscopic dissection to separate these units for transplantation in a fashion that most closely resembles naturally occurring hair. FUT has grown to become recognized by many prominent hair restoration surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…This is the first method that was performed for hair transplantation and it is still commonly used; however, it has some limitations [24]. For example, during the procedure, magnification is required to diminish graft transection and obtain suitable grafts for implantation [25,26]. This increases the duration of graft preparation and decreases the graft count.…”
Section: Discussionmentioning
confidence: 98%
“…This is the first method that was performed for hair transplantation and it is still commonly used; however, it has some limitations [24]. For example, during the procedure, magnification is required to diminish graft transection and obtain suitable grafts for implantation [25,26]. This increases the duration of graft preparation and decreases the graft count.…”
Section: Discussionmentioning
confidence: 98%
“…[16][17][18][19] As stated by Rousso and Presti, 'the technique is only as effective as the technician, and results are heavily dependent on the forethought of the architect' . For those patients who would prefer hair restoration to proceed, the principal techniques used are surgical: tissue expansion, scalp reduction and hair transplantation.…”
Section: Local Flapsmentioning
confidence: 99%
“…One study found that men treated with the HairMax Laser Comb three times a day for 26 weeks had increased hair density compared with a control group using a sham device [129]. Various other modalities of low-level laser therapy are being investigated [134]. One study involving seven patients treated with a laser helmet over a period of 3-6 months failed to show statistical significance [133].…”
Section: Low-level Laser Therapymentioning
confidence: 99%